Dexamethasone and granulocyte colony-stimulating factor alter the representation of cellular patterns and neurotisation of regenerative neuroma - O. M. Grabovyi; N. M. Nevmerzhytska; O. B. Alyokhin; H. B. Kostynskyi; H. Yu. Kondaurova (Zaporozhye State Medical University, 2023)
Aim. To evaluate the changes in the total cellularity (Nuc) of the rat sciatic nerve regenerative neuroma (RegN) and its representation of CD90, CD44, CD146, and CD133 positive cells, as well as its neurotization under the conditions of dexamethasone (Dex) and granulocyte colony-stimulating factor (GCSF). Materials and methods. After injections of dexamethasone and granulocyte colony-stimulating factor in the regenerative neuroma of 168 male Wistar rats, CD90, CD44, CD146 and CD133 positive cells were detected immunohistochemically in the regenerative neuroma. Its total cellularity and neurotization were determined and statistical processing of the obtained data was performed. Results. It was found that dexamethasone and granulocyte colony-stimulating factor change the representation of cellular patterns and neurotization of regenerative neuroma. Conclusions. The amount of neurotization of the regeneration neuroma directly depends on the specific amount of Schwann cells in its composition. Dex and GCSF, despite different mechanisms of action, lead to an increase in the content of neuroleumocytes in RegN.